Gendered Discourse in The Ballad of Songbirds and Snakes (2023): A Comparative Analysis of Male and Female Language Features - Kharisma Tri Fajarwati; Wulan Rahmatunisa; Vina Agustiana (Journal of English Language Teaching, Linguistics, and Literature (JETLEE), 2026)
This study explores gendered communication patterns through the analysis of language features used by male and female characters in The Ballad of Songbirds and Snakes movie. Employing Jennifer Coates’s (2015) framework, seven language features—minimal responses, hedges, tag questions, questions, commands and directives, swearing and taboo language, and compliments—were examined to identify distinctions in male and female speech. The study adopted a qualitative method with a case study design. A total of 143 male and 85 female utterances were analyzed. Findings indicate that male characters predominantly used questions (52.54%) and commands/directives (17.48%), reflecting a more assertive and directive communication style. In contrast, female characters employed more hedges (25.88%) and compliments (5.88%), suggesting a more cooperative and supportive style of interaction. These findings support Coates’s claim that male speech often emphasizes control and competitiveness, while female language tends to prioritize relational maintenance. This analysis not only illustrates how gendered language reinforces traditional gender ideologies but also demonstrates how dystopian media narratives can mirror broader societal power structures. By adopting a consistent theoretical lens, this research provides analytical rigor and enhances comparability between male and female speech. The study contributes to sociolinguistic scholarship by offering insights into the representation of gender in cinematic discourse and may inform future investigations into language, media, and identity construction.